TARI KREASI TRADISIONAL JAWA DALAM MENURUNKAN PERILAKU HIPERAKTIF ANAK USIA DINI - Dani, Robik Anwar; Marcella Mariska Aryono (Bajang Institute, 2024)
Hyperactivity is usually characterized by a tendency to carry out motor activities excessively and without purpose, resulting in difficulty in completing structured tasks and adapting to the demands of certain situations. This research aims to determine the effectiveness of applying traditional Javanese creative dance therapy in reducing hyperactive behavior in early childhood. One method that can be applied is dance movement therapy. This research is a quantitative experimental research. The experimental design used is a single case design with A-B-A. Data analysis was carried out using statistical analysis using the Wilcoxon test and graphic trend analysis of the results of filling in the behavior checklist to determine the effectiveness of traditional Javanese creative dance therapy interventions in reducing hyperactive behavior in early childhood. The results of this research are that dance movement therapy can reduce the level of hyperactive behavior in young children. This is evident from the data obtained for each subject which shows differences in hyperactive behavior scores at baseline one, intervention, and baseline two. When attending dance movement therapy intervention sessions, research subjects became calmer when attending class lessons. Likewise, the physical activities or movements carried out become more controlled and purposeful.